Eight weeks of phosphatidic acid supplementation in conjunction with resistance training does not differentially affect body composition and muscle strength in resistance-trained men - Andre, T. L.; Gann, J. J.; McKinley-Barnard, S. K.; Song, J. J.; Willoughby, D. S. (Journal of Sports Science & Medicine, 2016)
This study attempted to determine the effects of eight weeks of resistance training (RT) combined with phosphatidic acid (PA) supplementation at a dose of either 250 mg or 375 mg on body composition and muscle size and strength. Twenty-eight resistance-trained men were randomly assigned to ingest 375 mg [PA375 (n = 9)] or 250 mg [PA250 (n = 9)] of PA or 375 mg of placebo [PLC (n = 10)] daily for eight weeks with RT. Supplements were ingested 60 minutes prior to RT and in the morning on non-RT days. Participants` body composition, muscle size, and lower-body muscle strength were determined before and after training/supplementation. Separate group x time ANOVAs for each criterion variable were used employing an alpha level of = 0.05. Magnitude- based inferences were utilized to determine the likely or unlikely impact of PA on each criterion variable. A significant main effect for time was observed for improvements in total body mass (p = 0.003), lean mass (p = 0.008), rectus femoris cross-sectional area [RF CSA (p = 0.011)], and lower-body strength (p < 0.001), but no significant interactions were present (p > 0.05). Collectively, magnitude-based inferences determined both doses of PA to have a likely impact of increasing body mass (74.2%), lean mass (71.3%), RF CSA (92.2%), and very likely impact on increasing lower-body strength (98.1% beneficial). When combined with RT, it appears that PA has a more than likely impact on improving lower-body strength, whereas a likely impact exists for increasing muscle size and lean mass.